Mechanical Behavior of Multi-Material Single-Lap Joints under High Rates of Loading Using a Split Hopkinson Tension Bar - Pascal Rüthnick; Noah Ledford; Mathieu Imbert; Michael May (Metals, 2022)
In the presented research, a split Hopkinson tension bar (SHTB) was used to measure the mechanical response of multi-material single-lap joints in the high-rate loading regime. High-performance applications require high-quality measurements of the mechanical properties to define safe design rules. Servo-hydraulic machines are commonly used to investigate such small structures, but they are prone to produce oscillation-affected force measurements. To improve force–displacement measurements, an SHTB was chosen to investigate these joints. Three different kinds of joints were tested: multi-material bolted joints, multi-material bonded joints, and multi-material bonded/bolted joints. One substrate of the joints was made of aluminum (Al-2024-T3) and the other one was made of a laminated composite (TC250). A countersunk titanium bolt and a crash-optimized epoxy adhesive (Betamate 1496 V) were used to fasten the joints. A constant impedance mounting device was implemented to limit wave reflections and to improve the signal quality. Quasi-static experiments at a servo-hydraulic machine were performed to compare the data with the respective data from the high-rate loading conditions. The presented research shows that high-quality high-rate tests of multi-material single-lap joints can be achieved by employing an SHTB. With this high-quality measurement, a rate dependency of the mechanical behavior of these joints was identified. The dynamic increase (DI), which is the ratio of a high rate of loading over quasi-static loading, was measured for each of the joint types, where the dynamic increase in the max force was DI = 1.1 for the bolted, DI = 1.4 for the bonded, and DI = 1.6 for the bonded/bolted joints.